Getting started with beef & diary cattle - Thomas, Heather Smith , 1944- (Storey Publication, 2005)
A guide to raising beef and dairy cattle that explains how to pick the best cattle, with an overview of specific breed attributes and information on how size, color, body shape, hair length, and milking abilities make each more or less suitable to various needs